Blazing Cane : Sugar Communities, Class, and State Formation in Cuba, 1868-1959 - McGillivray, Gillian, 1971- (Book collections on Project MUSE., 2009)
Offers a new understanding of the history of Cuba from the mid-nineteenth century to the Cuban revolution by showing the national and transnational implications of local developments in two sugar mill communities.